<h3>
Answer: p = 0.12*(1.02)^t</h3>
Explanation:
The general exponential growth equation is
p = A*B^t
where t is the number of years that have gone by after 2008, A is the starting amount, B is the growth multiplier, and p is the price t years after 2008
We know that A = 0.12 is the starting price
The value of B is B = 1.02 which is in the form 1+r since 1.02 = 1 + 0.02 = 1+r
The r value is r = 0.02 and it is positive to represent growth. Keep in mind that 2% = 2/100 = 0.02
So we go from
p = A*B^t
to
p = 0.12*(1.02)^t
1.5 for each friend, plus who eats fruit bars xD
Answer:
2.8+.55x=5 x=4
Step-by-step explanation:
5-2.8=2.2
2.2/.55=4
It’s -4 and it’s -5.........
Answer:
67 the answer is 67 because u add it all up